The Effect of Single Leg Hurdle Hops and Alternate Jump Plyometric Exercises on the Speed of the Front Kick at the PSP Club (Pencak Silat Prestasi) Pekalongan City - Naufal Hilmy Al as’ad; Heny Setyawati; Hary Pramono; Muhammad Riski Adi Wijaya (BIRCU, 2021)
The purpose of this study was to analyze whether plyometric single leg hurdle hops and alternate jump had an influence on front kick speed. This is a quasi-experimental study using a Non-Randomized Pre-Post-Control Group Design. The population comprises 33 participants, while the sample comprises 33 participants. Saturated sampling was used to collect data. This study’s instrument was a front kick speed test (johansyah lubis). The paired sample t test was used to analyze the data, followed by the ANOVA test, all performed using the SPSS (Statistical Program for Social Science) 22.0 computer program. The paired sample t test results for single leg hurdle hops and varying jump speeds for right and left front kicks indicate that the significance level for each variable is sig 0.000 <0.05. ANOVA indicates that single leg hurdle hops have a plyometric effect on the right foot. Fcount 90.452> Ftable 4.46 and Fcount 151.111> left leg Ftable 4.46, plyometric alternate jump with right leg Fcount 63.380> Ftable 4.46 with left leg Fcount 93,389> As a result of Ftable 4.46, it can be concluded that there is a statistically significant difference in the results of single leg hurdle hops and alternate front kick speed jumps across three different groups, with a significance level of sig 0.05. The results of the post-hoc multiple comparisons (LSD) test of independent variables that have a significant effect on increasing the dependent variable showed that the single leg hurdle hops group achieved a right front kick speed of 5.454, while the left group achieved a speed of 6.181, indicating that single leg hurdle hops are more influential. Based on the analysis above, it can be concluded that each group of the single leg hurdle hops plyometric exercise group increases the speed of the right and left front kicks more than the alternate jump plyometric exercise group or the control group exercise.